Rare liverwort species of Romania from the exsiccatae of K. Loitlesberger - Ștefănuț, Sorin (Phytotaxa, 2020)
Within the framework of the Synthesys Programme, some European liverwort species held by the Herbarium of the Natural History Museum in Vienna (W) were checked, in particular for their occurrence in Romania. Examination of these liverwort specimens has led to the identification of rare species for Romania, some of which are only present in the Vienna collection. This includes the exsiccatae collections compiled by the bryologist Karl Loitlesberger for Romania, during his field trip in 1897 and held by W. In these exsiccatae, several rare species of liverworts have been identified and confirmed, such as Frullania parvistipula, the holotype of the taxon Marsupella lapponica, the male of Bucegia romanica (=Marchantia romanica), and Scapania crassiretis for Romania. This paper presents for the first time the oldest known drawings of Frullania parvistipula and Bucegia romanica.